Stock Market Liquidity and Stock Market Performance in Nigeria: Evidence from the Nigerian Exchange Limited - Alaba, John Stephen; Ahmed, Yahaya; Mopelola, Malik-Abdulmajeed, Kudirat; Hussain, Umar (iRASD Journal of Management, 2024)
Insufficient liquidity can become a significant obstacle to stock trading and impede the smooth operation and performance of the stock market. This motivated the study to investigate the effect of stock market liquidity on stock market performance in Nigeria. The research design employed was ex post facto, while stratified sampling technique was used to select top 30 actively traded and most liquid companies tagged NGX-30 for this study. Data were sourced secondarily from SEC Statistical Bulletin, CBN Statistical Bulletin and www.investing.com. The Vector Error Correction (VEC) System Equation Regression was employed as the estimation technique. The results revealed that liquidity depth, liquidity breadth, and liquidity immediacy have significant positive effects on stock market performance as shown by ? = 0.2019, 8.5594, 3.3268; p-value = 0.0329, 0.0052, 0.0467 respectively. Also, interest rate, inflation rate and exchange rate have varied significant effects on stock market performance as shown by ? = -0.0023, -1.1738, 0.03432; p-value = 0.0634, 0.0346, 0.0778 respectively. Therefore, the study concluded that stock liquid significantly affects stock market performance. Thus, the study recommended that the Security and Exchange Commission (SEC) should implement policies that encourage the participation of more traders to increase the number of actively traded stocks; support measures that improve the depth of the market by promoting transparency and fairness; improve the infrastructure for trade execution to enhance liquidity immediacy; and develop mechanisms to promptly identify and mitigate market risks.